Kinematics Analysis of Corn Hill-seeder based on 4-CRR Parallel Mechanism - Haibao Gao; Ruiqin Li; Fengping Ning; Zehui Li (Jixie chuandong)
A kind of corn hill-seeder based on 4-CRR parallel mechanism is presented. The degree of freedom of the 4-CRR parallel mechanism is solved by using screw theory，and verified by using the modified Kutzbach-Grübler formula. The inverse position solution of the mechanism is solved by using equivalent plane projection method，and the Jacobian matrix of the mechanism is derived to analyze its velocity. The value range of rod length of 4-CRR parallel mechanism applied to hill-seeder is analyzed. The workspace of the mechanism with a rod length of 250 mm is solved by the limit boundary search method. The moving platform of the mechanism can realize translation movements along the three coordinate axis directions. The interior of the workspace is continuous，and a 300 mm×300 mm adjustable seeding area can be formed below the hill-seeder. The hill-seeder based on 4-CRR parallel mechanism can flexibly adjust the sowing position and change the planting density according to the different soil conditions in the field to achieve the effect of increasing yield and income of corn.